2013
DOI: 10.1252/jcej.13we169
|View full text |Cite
|
Sign up to set email alerts
|

A Front-Tracking Method for Three-Phase Computations of Solidification with Volume Change

Abstract: We use a front-tracking method to simulate solidi cation with volume change of a droplet on a xed cooling plate. The problem includes temporal evolution of three interfaces, i.e., solid-liquid, solid-air, and liquid-air, that are explicitly tracked under the assumption of axisymmetry. The solid-liquid interface is propagated with a normal velocity that is calculated from the normal temperature gradient across the front and the latent heat. The liquid-air front is advected by the velocity interpolated from near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 15 publications
2
29
0
Order By: Relevance
“…2. 9. It can be observed that the large oscillations disappears quickly while the parts with smoother curvatures remain longer.…”
Section: Dependent On Local Curvaturementioning
confidence: 89%
See 4 more Smart Citations
“…2. 9. It can be observed that the large oscillations disappears quickly while the parts with smoother curvatures remain longer.…”
Section: Dependent On Local Curvaturementioning
confidence: 89%
“…For instance, an implementation of the geometric approach, also known as front tracking or marker particle method, has been developed recently for fluid interfaces in compressible flows [8], as well as an algorithm to simulate solidification with volume change of a droplet on a fixed cooling plate [9]. The VOF method is still used for many 10 (a) (b) applications too, such as the simulation of wall to liquid heat transfer [10] or the simulation of electrohydrodynamic two-phase flows [11].…”
Section: φ(γ(T) T) = 0 (23)mentioning
confidence: 99%
See 3 more Smart Citations